2021
DOI: 10.1038/s41598-021-86411-y
|View full text |Cite
|
Sign up to set email alerts
|

Mercury content in the Siberian tiger (Panthera tigris altaica Temminck, 1844) from the coastal and inland areas of the Russia

Abstract: Being a global pollutant, mercury can originate from both natural as well as anthropogenic sources. Coastal marine atmospheric fog is considered a potential source of ocean-derived monomethylmercury (MMHg) to coastal terrestrial ecosystems. However, the ratio between mercury appearing through natural processes and that from the results of human activity is unclear. We assumed that the total mercury content in the fur of tigers would differ depending on the distance from the sea. Here we show that the average m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…And this is four tenfold lower than in three Sorex species in Sikhote-Alin [30] and industrial areas of Europe and North America [15,13]. Sikhote-Alin located very close to the Pacific Ocean, so the sea fog may impact for the increase of the mercury concentration in terrestrial biota [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…And this is four tenfold lower than in three Sorex species in Sikhote-Alin [30] and industrial areas of Europe and North America [15,13]. Sikhote-Alin located very close to the Pacific Ocean, so the sea fog may impact for the increase of the mercury concentration in terrestrial biota [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study of various forms of mercury in the inanimate and living components of the ocean and land [7,8] showed that sea fog is a source of mercury for terrestrial ecosystems in California [9]. The assessment of the total mercury (THg) content in the Amur tiger fur in the Sikhote-Alin mountain system and in the Southwestern Primorye [10,11] confirmed the pattern established by Weiss-Penzias and co-authors [9]: the mercury level in the zone of influence of the sea is higher than in the inner zone [10,11]. At the same time, the south of the Russian Far East is of interest for the study of mercury due to the fact that gold, coal and mercury-containing minerals are actively mined in this region and in its neighborhood.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the south of the Russian Far East is of interest for the study of mercury due to the fact that gold, coal and mercury-containing minerals are actively mined in this region and in its neighborhood. In this region, pilot studies of the total mercury content in organs, tissues and fur of bears [12], wild cats [10,11], shrews [13] and deer [14] were conducted on small samples.…”
Section: Introductionmentioning
confidence: 99%